The future of isosorbide as a fundamental constituent for polycarbonates and polyurethanes - Olga Gómez-de-Miranda-Jiménez-de-Aberasturi; Ander Centeno-Pedrazo; Soraya Prieto Fernández; Raquel Rodriguez Alonso; Sandra Medel; Jose María Cuevas; Luciano G. Monsegue; Stefaan De Wildeman; Elena Benedetti; Daniela Klein; Hartmut Henneken; José R. Ochoa-Gómez (Green Chemistry Letters and Reviews, 2021)
Isosorbide is a biobased compound which could become in the near future an advantageous competitor of petroleum-derived components in the synthesis of polymers of different nature. When the reactivity of isosorbide is not enough, it can be successfully transformed into secondary building blocks, such as isosorbide bis(methyl carbonate), which provides extra functionalities for polymerization reactions with diols or diamines. The present review summarizes the possibilities for isosorbide as a green raw material to be used in the synthesis of polycarbonates and polyurethanes to obtain products of similar or enhanced properties to the commercial equivalents.